Assembling Mn:ZnSe quantum dots-siRNA nanoplexes for gene silencing in tumor cells. (24th September 2014) - Wang, Yucheng; Yang, Chengbin; Hu, Rui; Toh, Hui Ting; Liu, Xin; Lin, Guimiao; Yin, Feng; Yoon, Ho Sup; Yong, Ken-Tye
Abstract : In this work, we demonstrate the use of manganese doped zinc selenide QDs (Mn:ZnSe d-dots) for gene delivery in vitro . Abstract : In this work, we demonstrate the use of manganese doped zinc selenide QDs (Mn:ZnSe d-dots) for gene delivery in vitro . Specifically, the d-dots were prepared as nanoplexes for facilitating the intracellular delivery of small interfering RNA (siRNA) molecules to pancreatic cancer cells (Panc-1), thereby inducing sequence-specific silencing of oncogenic K-Ras mutations in pancreatic carcinoma. For nanoplex preparation, a layer-by-layer (LBL) assembling method was adopted to modify the d-dot surface with cationic polymer poly(allylamine hydrochloride) (PAH) or polyethylenimine (PEI) for generating positive surface potential for complexing with K-Ras siRNA molecules. Owing to the unique and stable PL properties of the d-dots, siRNA transfection and the subsequent intracellular release profile from the d-dot/polymer-siRNA nanoplexes were monitored by fluorescence imaging. Quantitative results from flow cytometry study suggested that a high gene transfection efficiency was achieved. The expression of the mutant K-Ras mRNA in Panc-1 cells was observed to be significantly suppressed upon transfecting them with the nanoplex formulation. More importantly, cell viability studies showed that the d-dot/PAH nanoplexes were biocompatible and non-toxic even at concentrations as high as 160 μg mL −1 . Furthermore, the amine-terminated surface could be further modified to obtain multiple bio-functions. Based on these results, we envision that the designed d-dot nanoplexes can be developed as a flexible nanoplatform for both fundamental and practical clinical research applications.